IMPROVING STUDENTS’ PUBLIC SPEAKING SKILLS THROUGH THE USE OF VIDEOTAPED FEEDBACK - Zulhermindra Zulhermindra; Hadiarni Hadiarni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
This study aimed to improve students’ public speaking skills at the English Education Department (JTBI) of IAIN Batusangkar through the use of videotaped feedback. The research was a Classroom Action Research (CAR) whose participants were the fourth semester students. The data were collected through observation, test, and interviews and were analyzed quantitatively and qualitatively. The findings shows that the use of videotaped feedback improved the students’ public speaking skills in which the average score increased from 6.95714 (Mid Term Test) to 7.026 (Final Test). This implies that there was an increase in the ability of students from the level of need improvement to the satisfactory. Even in the aspects of Introduction, Body, Conclusion and Time, which were the focuses of this class action research, there were increases from 7.38, 7.1, 6,8, and 6.6 (UTS) to 8, 7.5, 7,3 and 7.2 (UAS) respectively. It also means that there were increases in students’ public speaking skills in all four aspects, which were from satisfactory (Introduction, Body), and need improvement (Conclusion, Time) to good (Introduction), and satisfactory (Body, Conclusion and Time). It is expected that the results of this study can be applied to other aspects of public speaking skills and other similar subjects.